Dynamic interactions between GDP, renewable energy, innovation, and CO2 emissions in Finland: a fourier-augmented ARDL analysis - Georgescu, Irina; Kinnunen, Jani (Letters in spatial and resource sciences, 2024)
This study uses the novel Fourier-augmented ARDL (FARDL) to explore the impact of renewable energy (REN), the number of patent applications (PA) and GDP per capita on CO 2 emissions in Finland during 1990–2022. The findings reveal that in the long run, GDP rises CO 2 emissions, while REN and PA decrease CO 2 emissions. The FARDL short-run results indicate that both REN and PA have a significant negative impact on CO 2 emissions, suggesting that higher adoption of renewable energy and technological innovation contribute to emission reductions. However, GDP does not show a significant effect in the short run, which may indicate a decoupling of economic growth from environmental degradation in the short term. Furthermore, the study highlights the need for policies that promote technological innovation and increased investment in renewable energy to achieve sustainable carbon reduction in the long term.